Food production, state agencies and territory normalization in Argentina (Huellas, 2020)
In globalization, the increasing complexity and deepening of the territorial division of labor implies changes in state forms. In the Argentinean socio-spatial formation, regulation State policies intertwine with food companies’ stock systems, constituting the space conditions necessary for modernization processes. In this article, we analyze the link between actions developed by national state agencies and the circuits of the urban economy of fast-processing food in the Buenos Aires metropolis. In order to do this, we specially focus on a key variable from the period: normalization.
Keywords: territorial division of labor; State; cooperation circles; food